Efforts to Achieve Environmental Sustainability through Ecotourism - Singgalen, Yerik Afrianto; Sasongko, Gatot; Wiloso, Pamerdi Giri (Journal of Indonesian Tourism and Development Studies, 2019)
This paper will discuss specifically the effort of Kupa-Kupa Beach Cottage and Meti Beach Cottage managers to achieve environmental sustainability through the concept of ecotourism. Furthermore, private sector involvement and mixed marketing strategy will be discussed to describe how community empowerment and local community support as an essential factor in regional tourism development, especially in North Halmahera District. The research method used is qualitative with case study approach. This paper shows that the private sector tends to adopt a community-based ecotourism concept to achieve environmental sustainability and tourism sustainability itself. The government will act as a stimulus and catalyst that is synergistic with the needs of the private sector to provide tourism facilities according to tourists' preference. Kupa-Kupa Beach Cottage and Meti Beach Cottage managers seek to provide employment for local communities as part of a marketing strategy so that they are mutually beneficial.Keywords: Community empowerment, ecotourism, environmental sustainability, mixed marketing strategy, private sector involvement.Â